Survey Of Complaints And Factors Affecting Them In Firoozgar Hospital - Saeedeh Movahednia; Zeinab Partovishayan; Mahmoud Bastani (پیاورد سلامت, 2014)
Background and Aim: Complaint is the expression of dissatisfaction that needs a response and investigation. It is an effective tool to improve the quality of services. The aim of this study was the survey of complaints, factors affecting them, and the complaint process in Firoozgar Hospital. Materials and Methods: This was a retrospective descriptive study. All registered complaints, such as written, verbal and telephone complaints were reviewed in 2012. The data were extracted from the complaint forms of Firoozgar Hospital, which included several parts: personal information, ward name, person complained of, and explanations about the problem. Then, effective factors in complaints were classified and then analyzed by descriptive statistics. Results: The most frequent complaints were related to nurses (192 cases). Complaints about doctors were 171 cases. Inappropriate communication (23.64%) was at the top of patient complaints; and complaints about fees (14.18%) was the next. Among paraclinical and support units, installations unit had the highest number of complaints (52 cases).  Conclusion: Since inappropriate communication was the point being complained of more than any other issue, interventions in this area should be considered. Hospitals should identify the root of problems systematically.